PHYLOGENY of TWO AFRICAN GENERA of SAPOTACEAE - ENGLEROPHYTUM and SYNSEPALUM (2019)
Englerophytum and Synsepalum are two closely related genera of trees and shrubs from the African tropics. Previous molecular studies have shown that these genera collectively form a clade within the subfamily Chrysophylloideae (Sapotaceae). However, little is known about the inter-relationships of the taxa within the Englerophytum-Synsepalum clade. In this study, nuclear ribosomal DNA and plastid trnH-psbA sequences were used to estimate the phylogeny within the clade. Results indicate that the clade consists of six major lineages, two composed solely of taxa from the genus Englerophytum and four composed of taxa from the genus Synsepalum. Each lineage can be distinguished by suites of vegetative and floral characters. Leaf venation patterns, calyx fusion, style length and staminodal structure were among the most useful characters for distinguishing clades. Some of the subclades within the Englerophytum-Synsepalum clade were also found to closely fit descriptions of former genera, most of which were described by Aubréville, that have since been placed in synonymy with Englerophytum and Synsepalum. The clade with the type species of Englerophytum also contains the type species of the genera Wildemaniodoxa and Zeyherella, which are confirmed as synonyms. © Trustees of the Royal Botanic Garden Edinburgh (2019).